Counselling within Inuit Systems in Canada’s North - Brooker, Anya (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2015)
This article builds upon limited resources available to support counsellors working with the Inuit population in Nunavut, Canada. The author discusses the history of Inuit culture with a focus on the intergenerational trauma that stemmed from colonialism, forced assimilation, and the Canadian government’s sovereignty efforts. This article addresses the loss of cultural identity that resulted among Inuit people due to these events. An analysis of current statistics and drawing on literature that discusses differences between Northern and Southern Canada reveals the stark prevalence of psychosocial issues such as drug and alcohol abuse and family violence. The modernization of society has contributed to the gap between traditional and modern Inuit culture. This population is in a state of cultural transition and therefore requires culturally sensitive and knowledgeable counsellors. It is the position of the author that by using a family systems therapy approach, the interventions would more closely align with Inuit values and therefore be the best choice when counselling Inuit clients.